A Multidimensional Perspective on Individual Differences in Multilingual Learners’ L2 Chinese Speech Production - Sun, Peijian Paul; Zhang, Lawrence Jun (Frontiers in Psychology, 2020)
To date, research has been undertaken to reveal factors contributing to learners’ L2 speaking and/or learning at particular points in time in separate studies from cognitive, affective, and socio-cultural perspectives as individual variables. Nonetheless, little research has concurrently investigated L2 speaking with the same cohort of learners as participants from these perspectives concurrently in a single study to obtain comprehensive and systematic understandings of how the three dimensions of factors work together in influencing individuals’ L2 speaking. This study, utilizing Segalowitz’s (2010) L2 speech production framework as the theoretical lens, examined a group of L2 Chinese multilinguals’ perceptions towards their speech performance and production ability development, attempting to uncover comprehensively and systematically the factors influencing L2 speaking from the three perspectives mentioned above. We collected data through focus groups and semi-structured interviews from 17 advanced level L2 Chinese multilinguals. The findings of the study revealed that factors that influenced the L2 Chinese multilinguals’ speech performance and their development of such an ability included the following: 1) age of acquisition, cognitive fluency, learning styles, and speaking strategies; 2) motivation, anxiety, speaking self-efficacy, and willingness-to-communicate; 3) L2 cultural interest, L2 communities, and L2 classes; and 4) multilingualism. We conclude that the development of L2 Chinese speech production ability could be the result of the synergies gained from the cognitive, affective, and socio-cultural dimensions of L2 learning and use. Insights into L2 Chinese teachers and learners in terms of how to support and sustain the improvement of L2 Chinese speech production ability are also discussed.